Mainstreaming Climate Policy: The Case of Climate Adaptation and the Implementation of EU Water Policy. (February 2013) - Brouwer, Stijn; Rayner, Tim; Huitema, Dave
Despite the fact that mainstreaming of climate change into existing EU sectoral policies is a key aim, empirical knowledge of how it works in practice remains scarce. With this paper we explore the degree to which climate considerations are taken into account in the implementation of one of the most influential pieces of European water legislation, the Water Framework Directive and, more importantly, we assess possible explanations for the geographical variability in levels of mainstreaming observed. Our empirical research is based on an analysis of both EU and local policy documents, as well as more than forty in-depth interviews, and shows that, for various reasons, the degree of mainstreaming that has taken place differs widely. We conclude that timely incentives and clear guidance will be necessary to ensure progress is made by all, but that a residual fear that the adaptation agenda is open to abuse by those seeking to rationalise failures to fully implement the Water Framework Directive has put a brake on the mainstreaming agenda.